Large artery: an important target for cerebral small vessel diseases - Xu, Wei-Hai (AME Publishing Company, 2014)
Large arteries are the upstream vessels of cerebral small vessels, through which blood flow is transported. Since structurally and functionally connected, large arteries and cerebral small vessels are physiologically correlated. However, large vessel diseases and small vessel diseases are investigated separately in old era. More and more evidence suggested they are inter-mingled and should be considered together. When a deep brain lacunar infarct occurs, it is of necessity to perform high-resolution magnetic resonance imaging to screen intracranial large artery atherosclerosis, which requires more intensified treatment. It may be the appropriate strategy to keep longitudinal monitoring of the trend of large artery stiffness and give intervention such as aggressive blood pressure control to prevent cerebral white matter lesions (WMLs) occurrence or progression. More data from cohort studies are required, especially the biomarkers of “diseased” artery stiffness. In the future, when randomized clinical trials are performed, the end points should take both large artery and small vessel damages into consideration. The two diseases are in the same “boat”, i.e., the pan-vessel diseases. In order to save one, we have to save both.